Entrepreneurial activities and models of advanced European science and technology universities. Issue 12 (31st May 2019) - Ricci, Riccardo; Colombelli, Alessandra; Paolucci, Emilio
Abstract : Purpose: The purpose of this paper is threefold. It is aimed at identifying: a broad set of entrepreneurial activities; different university entrepreneurial models; and the entrepreneurial best practices of advanced European S&T universities. Design/methodology/approach: The paper has adopted a mixed-method design. By mainly relying on primary data, collected through questionnaires and interviews with those in charge of the technology transfer offices of 20 universities belonging to the CESAER association, the empirical analysis has combined both quantitative and qualitative approaches. Findings: The results of the empirical analysis have allowed five entrepreneurial activities to be identified. Three main entrepreneurial university models, based on different configurations of entrepreneurial activities, on different organisational and ecosystem characteristics and on a set of entrepreneurial best practices: an "engage" model, which focusses on local economic development; a "formal" model, which focusses on the financial advantage of universities and their faculties; and a "comprehensive" model, which focusses on the local economic development and the financial advantage of universities and their faculties. Research limitations/implications: The first limitation of the present paper concerns the limited number of sampled universities. Moreover, this paper is limited to the European area. Future research could enlarge this study by increasing the number of universities and by focusing on other geographical areas. Furthermore, the paper does not assess the effectiveness of the identified entrepreneurial models in supporting entrepreneurship and local economic development. Further research could extend the present analysis and fill these gaps. Originality/value: The paper contributes to the extant literature under many respects. First, it relies on original primary data. Moreover, it extends previous literature by encompassing the conventional distinction between formal and informal entrepreneurial activities. It also contributes to the emerging literature on entrepreneurial university models and the strategic approaches by identifying the different models of entrepreneurial universities in the European setting of S&T universities focusing on the role played by organisational and regional factors in affecting the adoption of a specific model by universities.